IMPLEMENTATION OF THE METER-BUS PROTOCOL FOR MEDIUM AND LOW VOLTAGE INDUSTRIAL MEASURING AND MONITORING UNITS - Villavicencio Chávez, Franz Josef (My University, 2012)
The main objective of this thesis work covers the design and implementation stages of the Meter-Bus (M-Bus) protocol having as target devices the VAMP96 medium and low voltage industrial measuring and monitoring units developed by VAMP Oy. The latest design platform, denominated G5-platform, of the target devices was used. The implementation of the M-Bus protocol includes both the development of its software and hardware instances. Software instance of the M-Bus protocol covers the set of functions and procedures—written in the C-Programming language—required for making possible the exchange of data, remote setup and control between these measuring units (M-Bus subunits) and a higher hierarchy main unit. This instance also deals with the development of two user interfaces targeting both the local display of a VAMP96 device and VAMPSET soft-ware application; the primary task of these interfaces is to facilitate the access of users to the configuration parameters of the VAMP96 devices. Hardware instance deals with the implementation of an embedded M-Bus subunit-specific physical layer by means of developing a reliable and low power consumption opto-isolated communication link between any M-Bus main unit and the microcontroller of a VAMP96 device. This instance also covers the design and development of an optional external communication module with the purpose of allowing the future use of the M-Bus protocol in other VAMP devices and their integration to M-Bus systems. The secondary target of this thesis is the implementation of the M-Bus protocol, by means of using third party protocol converter, for VAMP96 devices having their former design platform (its protocol suite lacks of M-Bus). The realization of the main objective in this research work constitutes the base upon which the first official release of the M-Bus protocol lies as an addition to the protocol suite in devices based on the G5 design platform.
Keywords: Meter-Bus Main unit; subunit; VAMP96; communication protocol; fi=Automaatiotekniikka|en=Automation Technology|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|